(untitled) (REMUNOM, 2025)
Substance-induced psychosis refers to symptoms that arise as a result of the physiological effects caused by an exogenous substance on the central nervous system. This disorder develops from intoxication or withdrawal resulting from the use of substances of abuse and can trigger episodes of hallucinations, delusions, and psychomotor disturbances. A significant portion of patients who experience their first episode of drug-induced psychosis end up developing a chronic psychotic disorder. In this context, this work aims to investigate the interactions related to the misuse of psychoactive substances with abuse potential and the triggering of psychotic disorders. The research was conducted through literature reviews from the following databases: National Library of Health (BVS) and U.S. National Library of Medicine (PubMed). Studies published between 2015 and 2025 that directly addressed the topic and the mechanisms involved were included. The results indicated that substances such as cannabis and amphetamines are strongly associated with the induction and worsening of psychotic episodes. Early and continuous use proved to be a determining factor in the severity of symptoms and the progression of induced psychosis to chronic disorders, such as schizophrenia. Thus, drug abuse acts as a triggering and potentiating factor for psychotic illnesses, reinforcing the need for preventive strategies and specialized clinical follow-up